KAJIAN SANAD, MATAN DAN SYARAH HADIS TENTANG HUKUM BARANG TEMUAN - SAMPARA PALILI (STIT Sunan Giri Bima, 2020)
This article examines the sanad, matan and shari'ah traditions about the law of found items. The method used is library research using a descriptive normative approach that emphasizes the analysis of data sources found. The hadith on the found law was narrated by 1) al-Bukhari in his Sahih 2) Muslims in his Sahih, 3) al-Tirmidhi in his Sunan, 4) Abu Dawud in his Sunan 5) Ibn Majah in his Sunan 6) Malik in al-Muatha 7) Ahmad bin Hanbal in his Musnad. The results of the study found that if someone found an item, he should not dare to take it unless he knew that he could be trusted in guarding it and was able to announce it until he found the owner. Anyone who feels that he cannot be trusted with the goods, then he may not take it. If he takes it, then he is similar to someone who seizes the property of others. Because, he took other people's property from the side that he was not allowed to take it. Also because by taking it at that time, it means that there is an act of wasting someone else's property.